Planning the unplanned: The role of a forward scout team in disaster areas. (October 2016) - Tarif, B.; Merin, O.; Dagan, D.; Yitzhak, A.
Abstract: Planning the mode of operation, manpower, and equipment, for a foreign medical team in a disaster-stricken area can be a difficult task, due to the chaotic nature of disasters. The important objective of arriving to the disaster-stricken area as soon as possible, in order to assist to as many victims as possible, is in constant tension with another important objective of arriving fully equipped and ready to such areas. Forward disaster scout teams (FDSTs) dispatched a few hours after the disaster are able to help plan foreign medical teams (FMTs) by gathering and relaying preliminary information after performing a situation analysis, locating the site of deployment for the FMT, and enabling logistic self-sufficiency. The purpose of this article is to share the lessons we have learned from our relatively long-standing experience of deployments in disaster-stricken areas. We also recommend a "to-do" checklist for FDSTs so that they perform their task of facilitating FMT readiness effectively.